Transanal rectosigmoid resection via natural orifice translumenal endoscopic surgery (NOTES) with total mesorectal excision in a large human cadaver series - Telem, Dana A.; Han, Kyung Su; Kim, Min-Chan; Ajari, Ifode; Sohn, Dae Kyung; Woods, Kevin; Kapur, Varun; Sbeih, Mohammad A.; Perretta, Silvana; Rattner, David W.; Sylla, Patricia (Surgical endoscopy, 2013)
Background The authors’ group has previously described successful transanal rectosigmoid resection via natural orifice translumenal endoscopic surgery (NOTES) in both porcine and cadaveric models using the transanal endoscopic microsurgery platform. This report describes the largest cadaveric series to date as optimization of this approach for clinical application continues. Methods Between December 2008 and September 2011, NOTES transanal rectosigmoid resection with total mesorectal excision (TME) was successfully performed in 32 fresh human cadavers using transanal dissection alone ( n = 19), with transgastric endoscopic assistance ( n = 5), or with laparoscopic assistance ( n = 8). The variables recorded were gender, body mass index (BMI), operative time, length of the mobilized specimen, integrity of the mesorectum and the resected specimen, and complications. Univariate statistical analysis was performed. Results Of the 32 cadavers, 22 were male with a mean BMI of 24 kg/m 2 (range 16.3–37 kg/m 2 ). The mean operative time was 5.1 h (range 3–8 h), and the mean specimen length was 53 cm (range 15–91.5 cm). After the first five cadavers, specimen length significantly improved, and a trend toward decreased operative time was demonstrated. The mesorectum was intact in 100 % of the specimens. In nine cadavers, endoscopic dissection was complicated by organ injury. Evaluation by the operative approach demonstrated a significantly longer specimen with laparoscopic assistance (67.7 cm) than with transgastric assistance (45.4 cm) or transanal dissection alone (49.2 cm) ( p = 0.013). Comparison of the technique used for inferior mesenteric pedicle division demonstrated both significantly decreased operative time (4.8 vs 6 h; p = 0.024) and increased specimen length (57.7 vs 39.6 cm; p = 0.025) when a stapler was used in lieu of a bipolar cautery device. Conclusion Transanal NOTES rectosigmoid resection with TME is feasible and demonstrates improvement in specimen length and operative time with experience. Transitioning to clinical application requires laparoscopic assistance to overcome limitations related to NOTES instrumentation, as well as procedural training with fresh human cadavers.